Impact Of Androgyne Influencer Use On Consumers Buying Interests On Social Media Instagram - Dudi Permana; Maria Ximenes (Clean and Sustainable Production, 2023)
Increased human activity has resulted in a decline in environmental quality. This condition leads to a greater impact on global warming. To minimize these negative impacts and improve sustainable quality of life, the Indonesian government has a strategic initiative in the form of sustainable resource allocation. The Indonesian government not only relies on government banks that can create financial stability, but also relies on local government banks that can create regional financial stability. In line with the Indonesian government's strategy, the study uses the SRI-Kehati Sustainability Index to analyze the relationship between state-owned bank lending and local government banks. Regression results show that Landesbanken has a relatively higher proportion of sustainable financing in the industrial sector at 13% than Landesbanken's 11%. However, state-owned banks contribute only 3% to the non-industrial sector, while local government banks contribute 6%. Moreover, the impulse response results show that compared to local government banks, state-owned banks have relatively more non-significant negative responses. When it comes to these results, no bank has had the greatest impact on building sustainable finance. However, both have their own merits in implementing appropriate sustainable financing when governments do not rely solely on government regulations and guidelines. However, securing enough financing and access to bank loans is expected to lead to better sustainable financing.